2019
DOI: 10.1093/mnras/stz1161
|View full text |Cite
|
Sign up to set email alerts
|

Cosmic ray transport and radiative processes in nuclei of starburst galaxies

Abstract: The high rate of star formation and supernova explosions of starburst galaxies make them interesting sources of high energy radiation. Depending upon the level of turbulence present in their interstellar medium, the bulk of cosmic rays produced inside starburst galaxies may lose most of their energy before escaping, thereby making these sources behave as calorimeters, at least up to some maximum energy. Contrary to previous studies, here we investigate in detail the conditions under which cosmic ray confinemen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
195
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(209 citation statements)
references
References 66 publications
11
195
1
2
Order By: Relevance
“…Similarly, Persic & Rephaeli (2014) determined the magnetic field strength to be 100 µG and also calculated the CRp energy density to be 250 eV cm −3 . Peretti et al (2019) found a magnetic field of 165 µG and a CR energy density of 425 eV cm −3 . Thompson et al (2006) estimated a maximum allowable magnetic field strength in the core of M82 of 1.6 mG, by balancing the magnetic energy density with that required for hydrostatic equilibrium, the total hydrostatic ISM pressure.…”
Section: Magnetic Field−gas Density Relationmentioning
confidence: 98%
“…Similarly, Persic & Rephaeli (2014) determined the magnetic field strength to be 100 µG and also calculated the CRp energy density to be 250 eV cm −3 . Peretti et al (2019) found a magnetic field of 165 µG and a CR energy density of 425 eV cm −3 . Thompson et al (2006) estimated a maximum allowable magnetic field strength in the core of M82 of 1.6 mG, by balancing the magnetic energy density with that required for hydrostatic equilibrium, the total hydrostatic ISM pressure.…”
Section: Magnetic Field−gas Density Relationmentioning
confidence: 98%
“…Advection of CRs directly into the wind escaping from starbursts may also play a role in determining their γ-ray spectrum and luminosity. Scenarios invoking advection in this context (e.g., Yoast-Hull et al 2013;Peretti et al 2019) have a number of points in their favour: starbursts do generally drive global winds (e.g., Veilleux et al 2005) whose speeds -in the 100s or even 1000s of km s −1 range -are large enough that advective escape can, prima facie, often compete with losses. Moreover, as for the ion-neutral-dampinglimited streaming discussed above, advective escape is an energy-independent process that can (over the CR energy range where advection is dominant over diffusion) explain the phenomenologically required hard γ-ray spectrum found in starburst systems.…”
Section: Diffusion Versus Advective Lossmentioning
confidence: 99%
“…One is that starburst galaxies, unlike the Milky Way or other spiral galaxies, are close to the limit of being calorimetric for protons, i.e., the majority of the energy injected into CR protons by shock acceleration is eventually converted to pions, the neutral fraction of which thence decay to γ-rays. Lines of evidence for this conclusion include both direct comparisons between γ-ray luminosities and star formation (and thus supernova) rates (e.g., Lacki et al 2011) and detailed modeling of the γ-ray spectrum (e.g., Paglione & Abrahams 2012;Yoast-Hull et al 2013, 2014Wang & Fields 2018;Peretti et al 2019). A second conclusion is that, again unlike in the Milky Way, CR escape from starbursts cannot be strongly energy-dependent, at least for CRs in the GeV to TeV energy range.…”
Section: Introductionmentioning
confidence: 99%
“…As discussed in [25], the timescale on which particle are advected in the AGN wind (τ adv = R out /v out ) is larger than the the residence time of CR protons and electrons in the central nuclear disk of the galaxy, while diffusion losses are not taken into account (see e.g. [42] for a description of diffusion losses in the nuclei of starburst galaxies). The latter constitutes a source of uncertainty in the computation of the maximum proton energy that we estimate to be E max ≃10-100 TeV.…”
Section: Agn Wind Modelmentioning
confidence: 99%